Experimental and numerical investigation of bulging behaviour of hyperelastic textured tubes. (September 2016) - Guo, Zhiming; Gattas, Joseph; Wang, Shibin; Li, Linan; Albermani, Faris
Abstract: The inflation and propagation of a localized instability in elastic tubes shares the same mathematical features with a range of other localization problems, including buckling propagation in long metal tubes under external pressure. Recent research into origami-inspired tubular geometries has suggested that geometric texturing is able to significantly improve metal pipe resistance to propagation buckling failures, with an increase in critical and propagation pressures. This paper aims to investigate whether texturing generates a similar improvement in hyperelastic tubes under axial loading and internal pressure, with elastomer origami structures of recent interest for use as soft actuators and robots. A new fabrication method with 3D printed moulds in a dip process was first developed to enable fabrication of textured tube samples. An experimental study was then conducted on inflated smooth and textured latex tubes, with instability formation observed at a 1 ms resolution. Comparative numerical models with a Mooney–Rivlin material were able to provide a good prediction of experimentally-observed behaviours up to and slightly past the critical pressure and bulge formation. A parametric numerical study is then conducted to show that the number of divisions in the axial direction and circumferential direction have no and modest effects on critical pressure, respectively. The experimental and numerical investigations both showed that the critical pressure of the textured tube was increased compared to the smooth tube, however the degree of increase was a modest 8% and so unlikely to be of significant practical benefit. This work can provide reference and guidelines for future investigations of tubular inflatable origami structures. Highlights: A new process for manufacture of latex origami-inspired textured tubes. Bulge formation and critical pressure experimentally investigated at 1 ms resolution. Textured geometry has only a slight increase in critical pressure compared to smooth tube. Parametric numerical study showed slight or no effect of textured tube parameters on critical pressure.